INTEGRATED PETROELECTRICAL MODELS OF DEVONIAN LIMESTONES AND CAMBRIAN SANDSTONES FROM DOBROTVIRSKA AREA OF VOLYNO-PODILIA - Vyzhva, S.; Onyshchuk, D.; Reva, M.; Onyshchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper deals with the technique and results of research into petroelectrical properties of complex terrigenous and carbonate reservoirs. Analyzed are electric data and their relation to capacity properties of Devonian limestones and Cambrian sandstones from Dobrotvirska area of Volyno-Podilia. The objective of the research was to build petroelectrical models of reservoir rocks based on the electrical parameters and their relation to capacity properties. Data on specific resistivity of reservoir rocks were used for specifying the range of its variation for different types and groups of rocks. These data were also essential for identifying the stratigraphic horizons, cross-sections and facies, as well as finding the relationship between specific resistivity and a range of factors such as mineral composition, pore structure, substance phase ratio, electric field intensity and frequency, and resistivity variations with epigenetic transformation and metamorphic changes in rocks. Laboratory data on electrical resistivity of rocks made it possible to interpret the results of employing electrometric well logging methods and electric exploration. Petrophysical laboratory data enabled us to determine the following properties: rock density (dry and saturated with synthetic brine), effective porosity (nitrogen and synthetic brine saturation methods), residual water saturation factor (by centrifugation), permeability (nitrogen stationary filtration method), interval time (P-wave velocity) and resistivity. There were obtained laboratory data on specific resistivity of rock samples (dry, partly and fully saturated with synthetic brine) in atmospheric and in simulated in-situ conditions. We estimated the petroelectrical parameters of Cambrian sandstones and Devonian limestones from Dobrotvirska area to find an empirical correlation between petroelectrical parameters, porosity and permeability of the studied rocks. The correlations are mainly approximated by power function and serve as the basis for geological interpretation of geophysical data. Electrometric methods have proved to be a powerful tool in both laboratory and field rock studies, being efficient enough to provide extensive information on rock properties.